Freedom Of Thought In Saman Novel By Ayu Utami (1998): A Genetic Structuralism Approach - Libriani, Ika; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2014)
This study is aimed to show freedom of thought which is represented by all major and some minor characters in Saman novel by using genetic structuralism approach. It is done by establishing two objectives: the first is analyzing the novel based on its structural elements and the second is analyzing the novel based on the genetic structuralism approach This research is descriptive qualitative research. In this method, there are two types of data sources, namely primary and secondary data source. The primary data source is Saman novel written by Ayu Utami and translated by Pamela Allen in 2005. Meanwhile the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. Based on the analysis, the researcher draws the following conclusions. First, based on the structural analysis of each element, it shows that the character and characterization, setting, plot, point of view, style, and theme are related to each other and form a unity of good novel. Second, based on the genetic structuralism approach, there is a close relationship between the novel and the realities of Indonesian life. The novel is as an object in which the author presents her world view.